1998
DOI: 10.1021/la9713816
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Titanium Oxide Nanotube

Abstract: Nanotubes composed of various materials such as carbon, boron nitride, and oxides have been studied recently. In this report, the discovery of a new route for the synthesis of a nanotube made of titanium oxide is presented. Needle-shaped TiO2 crystals (anatase phase) with a diameter of ≈8 nm and a length of ≈100 nm were obtained when sol−gel-derived fine TiO2-based powders were treated chemically (e.g., for 20 h at 110 °C) with a 5−10 M NaOH aqueous solution. It was found by observation using a transmission el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
1,544
7
45

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 2,427 publications
(1,735 citation statements)
references
References 11 publications
39
1,544
7
45
Order By: Relevance
“…1.1). Titania nanotubes (n-TiO 2 ) can be fabricated using several techniques, including the assisted-template method [27], sol-gel method [28], electrochemical anodic oxidation method [29] and hydrothermal treatment [30]. …”
Section: Composite Reinforcement Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…1.1). Titania nanotubes (n-TiO 2 ) can be fabricated using several techniques, including the assisted-template method [27], sol-gel method [28], electrochemical anodic oxidation method [29] and hydrothermal treatment [30]. …”
Section: Composite Reinforcement Trialsmentioning
confidence: 99%
“…The temperature was controlled using a T-thermocouple and a temperature controller (Omega HRC5A). Samples of n-TiO 2 were synthesized using the alkaline hydrothermal technique described earlier by Kasuga et al [28]. Basically, the experiment was started by dispersing 0.24 g strontium acetate powder in 30 mL of 10 M NaOH solution and stirring for 24 h, followed by addition of 2 g of commercially available TiO 2 nanopowder and stirring for another 24 h. The mixture was transferred to a Teflon-lined stainless steel autoclave for hydrothermal treatment.…”
Section: Nanotube Synthesismentioning
confidence: 99%
“…Since Kasuga et al [1] described a novel hydrothermal method for titanate nanotubes (TNTs) formation, the investigations on preparation and properties of these species have attracted attention of numerous researchers. More than a decade later, the structure of TNTs as well as their properties are still a problem under discussion.…”
Section: Introductionmentioning
confidence: 99%
“…Lin [12] reported that TiO 2 powders used as the provider of raw material were corroded by strong acid, and the formation mechanism of nanotubes were in a dissolutionprecipitation-growing procedure. However, Wang et al [13] and T. Kasuga et al [14] discussed that during treatment with NaOH solution, some Ti-O bonds of the TiO 2 precursor were broken, leading to the formation of lamellar fragments that were the intermediate phase in the formation process of the nanotubes material. The tubular structure was achieved by rolling slowly after the acidic post-treatment process, and therefore the acid rinsing step had become very important during the TiO 2 nanotubes formation process.…”
Section: B Characterization Of Titanium Dioxide Nanotubementioning
confidence: 99%